Civics Learning in Improving Student Character Based on Islamic Boarding School Traditions - Khosiah, Nur; Fadilah, Yulina; Zainab, Siti (Universitas Muhammadiyah Sidoarjo, 2023)
Education in society in character formation has three normal qualities, including competence (communication skills, listening competence, and cooperation competence), will/desires, and good moral habits. Character building at M.I Nurul Ulum, Kerpangan Village, Leces District, Probolinggo Regency is one of the educational institutions under the auspices of the pesantren, and M.I Nurul Ulum adopts many activities and habits from the pesantren. This study aimed to find out Civics Learning at MI Nurul Ulum in improving student character in the tradition of the kerpangan village Islamic boarding school, Leces sub-district, Probolinggo district. The method used is descriptive qualitative with data collection techniques, observation, interviews, and documentation. Citizenship Education is a compulsory subject from elementary to tertiary education because Civics is the cultural moral of the Indonesian nation, which is based on the precepts in Pancasila and the 1945 Constitution. The characteristics expected from the pesantren tradition of Civics learning are our love for the motherland, compassion, love, peace, responsibility, independence, equality, honesty, and humility.Keywords: Civics Learning, Student Character